Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

I'm having a hard time setting up equations for the following problem:

A green hoop with mass $m_h$ and radius $r_h$ m hangs from a string that goes over a blue solid disk pulley with mass $m_d$ and radius $r_d$. The other end of the string is attached to a massless axel through the center of an orange sphere on a flat horizontal surface that rolls without slipping and has mass $m_s$ kg and radius $r_s$. The system is released from rest.

enter image description here

What is the magnitude of the linear acceleration of the hoop?

share|improve this question

2 Answers 2

From $F=ma$ we can simply find $a=F/m$. The important part is to remember in these type of questions we are looking for the sum, $\Sigma$, of all the appropriate accelerations to determine $a$. ie. $a_{total} = a_1 + a_2 +a_3$ ... etc.

share|improve this answer

You can solve this with the lagrangian formalism. Let the total length of the string be $x+y=l$. Now since the cylinder is rolling, we also know $x = \phi R$ with $R$ the radius of the cylinder and $\phi$ the angle it has rotated through. we then have a constraints $$ f_1 = x + y - l = 0\quad \text{and}\quad f_2 = x-R\phi =0 $$

Now consider the kinetic and potential energies of the system. For the cylinder, we have the typical $$ T=\frac{1}{2}I\dot{\phi}^2 + \frac{1}{2}M\dot{x}^2 $$ and for the hoop we then have $$ T = \frac{1}{2}m\dot{y}^2 $$ and $$ U = -mgy $$ Now use $$ \frac{d}{dt}\frac{\partial L}{\partial \dot{q}_{i}}-\frac{\partial L}{\partial q_i}=\sum_{j}\lambda_j \frac{\partial f_j}{\partial q_i} $$ with $\phi$ and $y$ and $x$ as your variables. I think this will let you solve this system. First let's consider the $\phi$ piece: $$ \frac{d}{dt}\frac{\partial L}{\partial \dot{\phi}}-\frac{\partial L}{\partial \phi}=\lambda_2 (-R)=I\ddot{\phi} $$ for the $x$ part we have $$ M\ddot{x} = \lambda_1+\lambda_2 $$ and for $y$ we get $$ m\ddot{y}-mg = \lambda_1 $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.